1996
DOI: 10.1111/j.1740-8261.1996.tb01232.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Identification and Characterization of Splenic Nodular Lipomatosis or Myelolipomas in Cheetahs (Acinonyx Jubatus)

Abstract: A total of 44 live cheetahs were examined sonographically between 1989 and 1994. Seventeen of these animals originated from 4 European facilities, the other 27 cheetahs were examined in 3 facilities in Namibia. Evaluation of the cheetahs included a clinical examination, abdominal ultrasound, and complete blood work. Splenic myelolipomas were diagnosed sonographically in 11 cheetahs. In 7 cheetahs the diagnosis was confirmed at necropsy. Nine of the 14 cheetahs in Europe had myelolipomas in the spleen, while in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…The hyperechoic nodules seen within the splenic parenchyma were consistant with the appearance of nodular myelolipomatosis 12,13,31 (also known as nodular lipomatosis), but this was not confirmed histologically. These fatty nodules are most likely incidental findings, although it has been suggested that as all the cheetahs in one study with nodular lipomatosis of the spleen also had concurrent chronic disease, nodular lipomatosis may be an indicator for chronic disease and/or stress 31 . In the latter study, 11 of 44 cheetahs had nodular lipomatosis of the spleen, of which nine of 17 were from European zoos and two of 27 were wild‐caught animals from Namibia 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hyperechoic nodules seen within the splenic parenchyma were consistant with the appearance of nodular myelolipomatosis 12,13,31 (also known as nodular lipomatosis), but this was not confirmed histologically. These fatty nodules are most likely incidental findings, although it has been suggested that as all the cheetahs in one study with nodular lipomatosis of the spleen also had concurrent chronic disease, nodular lipomatosis may be an indicator for chronic disease and/or stress 31 . In the latter study, 11 of 44 cheetahs had nodular lipomatosis of the spleen, of which nine of 17 were from European zoos and two of 27 were wild‐caught animals from Namibia 31 …”
Section: Discussionmentioning
confidence: 99%
“…As only two of the 21 cheetahs (9.5%) had hyperechoic ''sludge'' in the dependent aspect of the gall bladder, this may indicate that the normal captive-bred cheetah has a low incidence of gall bladder sludge, in contrast to the incidence of ultrasonographically evaluated sludge in 30 healthy dogs being 53%, decidedly higher than in this study. 30 The hyperechoic nodules seen within the splenic parenchyma were consistant with the appearance of nodular myelolipomatosis 12,13,31 (also known as nodular lipomatosis), but this was not confirmed histologically. These fatty nodules are most likely incidental findings, although it has been suggested that as all the cheetahs in one study with nodular lipomatosis of the spleen also had concurrent chronic disease, nodular lipomatosis may be an indicator for chronic disease and/or stress.…”
Section: Discussionmentioning
confidence: 99%
“…Myelolipomas are benign, often multiple, tumors of the spleen and occasionally the liver, composed of mature adipocytes (fat cells) mixed with hematopoietic cells (Munson, 1993;Munson et al, 1999). These tumors can be identified by ultrasound and have been mistaken for more malignant tumors resulting in unnecessary removal of the spleen (Walzer et al, 1996). Myelolipomas also occur in wild cheetahs (Mitchell, unpublished data).…”
Section: Neoplasiamentioning
confidence: 99%
“…These lesions were thought to represent small abscesses, possibly hyperechoic because of centralized hemorrhage, necrosis, or bacterial gas microbubble formation. [55][56][57][58][59] In questionable cases, an ultrasound-guided aspirate is indicated to determine if mast cells are present. Differential diagnosis must include hematoma, focal nodular hyperplasia with necrosis, and primary or metastatic neoplasia.…”
Section: Nodular Hyperplasiamentioning
confidence: 99%